7(-9a-4)=-2a-10(1+6a)

Simple and best practice solution for 7(-9a-4)=-2a-10(1+6a) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(-9a-4)=-2a-10(1+6a) equation:



7(-9a-4)=-2a-10(1+6a)
We move all terms to the left:
7(-9a-4)-(-2a-10(1+6a))=0
We add all the numbers together, and all the variables
7(-9a-4)-(-2a-10(6a+1))=0
We multiply parentheses
-63a-(-2a-10(6a+1))-28=0
We calculate terms in parentheses: -(-2a-10(6a+1)), so:
-2a-10(6a+1)
We multiply parentheses
-2a-60a-10
We add all the numbers together, and all the variables
-62a-10
Back to the equation:
-(-62a-10)
We get rid of parentheses
-63a+62a+10-28=0
We add all the numbers together, and all the variables
-1a-18=0
We move all terms containing a to the left, all other terms to the right
-a=18
a=18/-1
a=-18

See similar equations:

| 2/3n+5=15 | | 6-2(x-1)=-16 | | 17.5+14.2+14.2x=49.2 | | -2=-(1+4m)-2m | | 4(-2x+5)=28 | | 5(2d+8)=7(2d+) | | 6a-20+a(-3)=50 | | 7x2+21x-28=0 | | (9y÷14)+(3÷7)=(9÷14) | | C=x^2-5x+30 | | –6x–x+10=15–7x–5 | | 5(3x-2)+12-6x=-43 | | 5=x+4=8 | | 5(2x+8)^2=-80 | | 8x^+40x^2=O | | 3.5/h=-2 | | 5x+12x-2x=15-10 | | 3(3x+5)-12x-4=5 | | 12x+28x+15=0 | | -1x+6=x+14 | | 0.35x200=70 | | 5x+2=8x+4=15x-18 | | x2-7x-7=0 | | -1/4*7+3r=-1/8r | | 4x-7x+17=44 | | -1-(k-8)=23+k | | -3(6-10v-5v)=0 | | 4x-9=-3(x+8)-27 | | 2/3(-3x+9)=-2 | | x/13=3/5.79 | | -16x^2+185=0 | | 15/7=30/k |

Equations solver categories